THE CONTRIBUTION OF ISLAMIC RELIGIOUS EDUCATION IN THE DEVELOPMENT OF CIVILIZATION: KONTRIBUSI PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN PERADABAN - Alfan Nawaziru Zahara; Triyo Supriyatno; Samsul Susilawati (SOSIOEDUKASI, 2025)
The study of Islamic Education in the development of civilization is very important to be studied more deeply because it continues to be a lively study among scholars and has relevance in facing global challenges. This article aims to explain three main aspects: (1) The form and paradigm of Islamic Education in building civilization, (2) Internal and external factors that affect the implementation of Islamic Education, and (3) The implications of Islamic Education on the development of civilization, both positively and negatively. This research uses a library research method with a historical-sociological approach and is based on Islamic education theory and civilization. Data collection was carried out through literature studies, then analyzed using qualitative-descriptive analysis. The results of the study show that: (1) The form of Islamic education in building civilization consists of three main paradigms: traditional, modern, and integrative, (2) Influential internal factors include religious values, local culture, and educational policies, while external factors include globalization, technology, and political dynamics, (3) The implications of Islamic Education on civilization include positive impacts in the form of increasing morality, intellectuality, and social solidarity,  as well as negative impacts such as resistance to modernization, exclusivism, and limited adaptation to global changes. In conclusion, Islamic education has a significant role in building a dynamic civilization based on Islamic values, but it needs adaptation to remain relevant in the context of globalization.